2009
DOI: 10.1590/s1415-43662009000500005
|View full text |Cite
|
Sign up to set email alerts
|

Fertilização silicatada na severidade de brusone e na incidência de insetos-praga em arroz irrigado

Abstract: A ocorrência de brusone e insetos-praga tem limitado a produtividade de arroz irrigado na região tropical, razão que este trabalho foi conduzido com o objetivo de avaliar os efeitos do serpentinito calcinado e da volastonita na severidade de brusone, na incidência de insetos-praga e na produtividade de arroz no cultivo principal e na soca. Em casa-de-vegetação foram avaliados os efeitos das doses 0, 1, 2, 4 e 8 Mg ha-1 de serpentinito calcinado e volastonita na severidade de brusone nas folhas da cv. Metica 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(20 reference statements)
0
2
0
2
Order By: Relevance
“…A presença desse elemento é também expressiva em solos desenvolvidos de serpentinitos e itabirito. O teor diferencial desse metal nesses materiais de origem parece ser determinante dessas tendências nos solos (Curi, 1983;Monteiro, 2005;Santos et al, 2009). …”
Section: Resultados E Discussão Extrações De Mn Na Terra Fina E Argilaunclassified
“…A presença desse elemento é também expressiva em solos desenvolvidos de serpentinitos e itabirito. O teor diferencial desse metal nesses materiais de origem parece ser determinante dessas tendências nos solos (Curi, 1983;Monteiro, 2005;Santos et al, 2009). …”
Section: Resultados E Discussão Extrações De Mn Na Terra Fina E Argilaunclassified
“…Many studies have shown that silicon prevents and/ or delays the penetration of the pathogen through the formation of a mechanical barrier, composed of amorphous silica, depoused between the cuticle layer and the epidermis layer, in foliar cells, and also acts by systematically inducing the production of defense enzymes and proteins [45][46][47][48]. Other studies showed that bioagents act effectively on plant resistance to diseases, being able to control pathogens by antibiosis, parasitism, by competition of nutrients, producing enzymes that degrade pathogen structures and together activating latent defense mechanisms, inducing resistance in plants [28,29,49].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to observe that, though the importance of the chemical control, some alternative strategy for avoiding the excessive dependence of fungicides such as silicon use through silicate correctives in the soil has been studied as a possible auxiliary strategy of the disease control. Some research results indicate that the silicon would create a mechanic barrier to the fungus penetration (SANTOS et al, 2009;DATNOFF et al, 1997). FILIPPI et al (2007) verified in an experiment in a greenhouse, in spraying plants 18 days after the emergence with an isolated avirulent of Magnaporthe oryzae, induction of resistance to the virulent fungus, associated with a significant decrease of the disease severity.…”
Section: Rice Blast -Magnaporthe Grisea (Pyricularia Grisea = Pyriculmentioning
confidence: 92%